Comparison of treatment outcome of transforaminal and caudal epidural steroid injections for radiating low back pain - Garg, Sorabh; Singh, Jagdeep; Kaur, Chandanpreet; Singh, Rajdeep; Pookunju, Azhar (International Journal of Research in Orthopaedics, 2022)
Background: Low back pain is a common disorder. Nearly everyone is affected by it at some time during one’s life time. Corticosteroid injections showed early and moderate but unsustained improvements versus placebo in certain outcomes for lumbar radiculitis. Hence; the present study was undertaken for assessing and comparing the efficacy of transforaminal and caudal epidural steroid injections outcome for the treatment of lumbar radiculitis. Methods: The study was conducted prospectively on 60 patients (30 each) from 20-75 years of age. All the patients were divided into two groups; Group A included patients in which Transforaminal route was used while Group B included patients in which caudal route was used. Pain relief was assessed after the epidural steroid injection using visual analogue scale (VAS) and Oswestry disability index (ODI). Results: Mean VAS and mean ODI score for the patients of Group A was significantly lower in comparison to the patients of group B at post-last injection, 15 days post-last injection, 1-month post-last injection and 3 months post-last injection time interval. Conclusions: Transforaminal approach exhibited superior efficacy and should be performed with increasing frequency. Transforaminal epidural steroid injection also gave better quality of life.